Stroke survivors show an overestimation of their on-road driving performance - Daniel A. Schlueter; Gernot Horstmann; Kim L. Austerschmidt; Jessica Koenig; Maximilian Flieger; Thomas Beblo; Martin Driessen; Wolf Schäbitz; Max Toepper (Neurological Research and Practice)
Abstract Objectives Strokes are often accompanied by physical and cognitive impairments affecting driving safety. After the recommended period of abstinence from driving, the patient must decide whether his or her driving safety is still impaired, which requires a valid self-assessment of the own driving skills. At present, it is uncertain whether stroke survivors are able to provide a valid self-assessment. Methods 12 stroke patients and 17 healthy controls participated in this prospective longitudinal on-road study. All participants underwent repeated neuropsychological and standardized on-road assessment at 4-month intervals (2 and 6 months after the stroke in the patient group). Statistical analyses included repeated measures ANOVA, group comparisons and correlation analyses. Results Our results revealed that in stroke survivors compared to healthy drivers, the validity of self-assessment (VSA) of the own on-road driving performance is impaired in the direction of overestimation (at both time points). In addition, the VSA of stroke survivors at second time point correlated with driving-relevant cognitive and non-cognitive measures. Discussion Our results suggest that the VSA of the own driving competence is impaired after stroke. Other than expected, the differences between stroke survivors and healthy drivers did not disappear within the 4-months-interval. Consequently, an impaired VSA in stroke survivors must be considered before deciding to let them drive again.